Will the Clean Development Mechanism Mobilize Anticipated Levels of Mitigation? - Rahman, Shaikh M.; Dinar, Ariel; Larson, Donald F. (2012)
Under the Kyoto Protocol, developed countries can only tap mitigation opportunities in developing countries by investing in projects under the Clean Development Mechanism. Yet Clean Development Mechanism investments have so far failed to reach many of the high-potential sectors identified by the Intergovernmental Panel on Climate Change. This raises doubts about whether the Clean Development Mechanism can generate an adequate supply of credits from the limited areas where it has proved successful. This paper examines the current trajectory of mitigation projects entering the Clean Development Mechanism pipeline and projects it forward under the assumption that the diffusion of the Clean Development Mechanism will follow a path similar to other innovations. Projections are then compared with pre-Clean Development Mechanism predictions of the mechanism s potential market size to discern whether limits on the types of projects entering the pipeline have limited the expected supply of certified emission reductions. Parameter tests suggest that this is not the case and that currently identified Clean Development Mechanism investments will generate offsets in excess of early model predictions. In particular, under favorable circumstances, the mechanism is on track to deliver an average annual flow of roughly 700 million certified emission reductions by the close of 2012 and nearly to 1,100 million certified emission reductions by 2020.